Effect of Long-Term Exposure to Ambient Fine Particulate Matter (PM2.5) on the Incidence of Type 2 Diabetes Mellitus (T2DM): A Cohort Study in Rural China - Yu, Cindy (Université d'Ottawa / University of Ottawa, 2020)
BACKGROUND: Long-term exposure to fine particulate matter (PM2.5) has been identified as a potential risk factor for developing type 2 diabetes mellitus (T2DM). Given the rising prevalence of T2DM and unhealthy concentrations of PM2.5 in China, our attention is brought to examining the association in this region of the world. Furthermore, rural China, although largely ignored, also finds itself suffering from increased risks of T2DM and high levels of PM2.5. OBJECTIVE: The goal of this study is to characterize the relationship between long-term exposure to PM2.5 and the risk of T2DM in rural China. We do so by confirming that greater long-term exposure to PM2.5 is associated with a higher risk of T2DM incidence, assessing the potential multiplicative and additive interactions with important covariates, and identifying constituents of PM2.5 that may be responsible for the effect PM2.5 on the increased incidence of T2DM. CONCLUSIONS: Greater long-term exposure to PM2.5 is associated with increased risk of developing T2DM in rural Deqing County, Zhejiang, China. Smoking status modifies the relationship between PM2.5 and T2DM incidence on a multiplicative scale. There is no synergism between smoking and PM2.5 in association with T2DM incidence. There is no conclusive evidence on which constituents of PM2.5 play greater roles in the adverse effects of PM2.5 on T2DM incidence.
Keywords: Epidemiology; Air pollution; Type 2 diabetes mellitus